Analisis Sektor Basis Dan Sektor Non Basis Pada Wilayah Kabupaten Bojonegoro Dan Kabupaten Tuban Di Provinsi Jawa Timur Menggunakan Metode Location Quetient, Shift Share, Dan Tipologi Klassen - Youlanda Sara Chumayda; Marseto Marseto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study was conducted with the aim of determining the base sector and non-base sector in Bojonegoro Regency and Tuban Regency. This research is based on secondary data in the form of time series data obtained through the Central Statistics Agency website in 2022 and processed using Location Quetient, Shift Share, and Klassen Typology analysis tools. And obtained the results of the analysis there are two base sectors in Bojonegoro Regency and three base sectors inTuban Regency. Keywords: Base Sector; Location Quetient, Shift Share, and Klassen Typology